Comprehensive Analysis of miRNAs and Target mRNAs between Immature and Mature Testis Tissue in Chinese Red Steppes Cattle - Xibi Fang; Lihong Qin; Haibin Yu; Ping Jiang; Lixin Xia; Zhen Gao; Runjun Yang; Yumin Zhao; Xianzhong Yu; Zhihui Zhao (Animals, 2021)
This study aims to screen potential regulators and regulate fecundity networks between microRNAs (miRNAs) and target genes. The bovine testes of immature and mature Chinese Red Steppes were performed by genome-wide analysis of mRNAs and miRNAs. Compared with testicular tissues of newborns, 6051 upregulated genes and 7104 downregulated genes in adult cattle were identified as differentially expressed genes (DEGs). The DEGs were significantly enriched in 808 GO terms (p < 0.05) including male gonad development, male genitalia development, spermatogenesis, and sperm motility. Moreover, DEGs were also significantly enriched in 105 KEGG pathways (p < 0.05), including cGMP-PKG signaling pathway and calcium signaling pathway. To explore the expression of miRNA-regulated gene expression, 896 differentially expressed target genes negatively regulated with the expression levels of 31 differentially expressed miRNAs (DERs) were predicted and analyzed, and a network-integrated analysis was constructed. Furthermore, real-time PCR was performed to verify the expression levels of DEGs and DERs. Our results identified novel candidate DEGs and DERs correlated with male reproduction and intricate regulating networks between miRNAs and genes, which will be valuable for future genetic and epigenetic studies of sperm development and maturity, as well as providing valuable insights into the molecular mechanisms of male fertility and spermatogenesis in cattle.